Acoustic study of an air intake system of si engine using 1-dimensional approach - Dahlan, A. A. (Universiti Malaysia Pahang, 2019)
Air intake system of an internal combustion engine plays main role in delivering fresh air from the environment to the engine and dampening the sound of the engine combustion process coming from the engine combustion process. In this study, a simulation was conducted to improve the existing air intake system design in terms of acoustic study to have better sound quality by modifying the resonators, air duct and airbox volume of the air intake module. This study implements the 1-dimensional simulation study using commercial software, correlate to the 1.6-liter natural aspirated engine. The objective of this study is to decrease the engine noise at snorkel of the air intake module without losing too much of pressure drop. At the end of this study, the analysis defines the geometry of air intake module with the recommended resonator for fabrication and physical testing. The simulation result shows that the modified air intake module meet the objective and fulfil the performance target.